P-type semiconductor surfactant modified zinc oxide nanorods for hybrid bulk heterojunction solar cells - Ben,Dkhil S; Gaceur,M; Dachraoui,W; Hannani,D; Fall,S; Brunel,F; Wang,M; Poize,G; Mawyin,J; Shupyk,I; Martini,C; Shilova,E; et al. (Solar Energy Materials and Solar Cells, 2016)
In this work, hybrid bulk heterojunction solar cells based on surfactant-modified zinc oxide nanorods (ZnO NRs) blended with poly-(3-hexylthiophene) (P3HT) are presented. (E)-2-cyano-3-(5′-(4-(dibutylamino)styryl)-2,2′-bithiophen-5-yl)acrylic acid (1), a p-type semiconductor, is used as grafted interfacial surfactant on ZnO NRs, named 1-ZnO NRs, in order to improve simultaneously the nanoscale morphology of the hybrid polymer blend as well as the electronic properties of the heterojunction interface. Our studies reveal that the ligand modification of ZnO NRs leads to strongly improved aggregate free P3HT/ZnO blends that show five time increased power conversion efficiency and corresponding photo-generated charge carrier transport compared to untreated ZnO NRs. From transient absorption spectroscopy, it was found that recombination kinetics were similar in the device using untreated ZnO and modified 1-ZnO NRs, respectively, pointing to a major impact of the ligand in the improvement of the blend morphology. Corresponding device optimization led to improvements of FF and Voc to values comparable to P3HT blends using fullerene acceptors, but photocurrent density of the P3HT/1-ZnO solar cells was found low even after optimization. The latter could be addressed to destruction of long range organization of P3HT induced by the presence of the ZnO NRs as well as low electron transport inside the blend.